40 years of cardiac rehabilitation and secondary prevention in post-cardiac ischaemic patients. Are we still in the wilderness?. (20th January 2015) - Jelinek, Michael V.; Thompson, David R.; Ski, Chantal; Bunker, Stephen; Vale, Margarite J.
Abstract: Cardiac rehabilitation (CR) is the sum of interventions required to ensure the best physical, psychological and social conditions so that patients with cardiac disease may assume their place in society and slow the progression of the disease. Exercise testing (ET) early after MI has been shown to result in earlier return to work than the non-performance of ET. Research quality CR has resulted in lower cardiovascular mortality and lower recurrent hospitalisation and has been shown to be cost-effective. However, the content of cardiac rehabilitation programmes varies considerably. The only randomised trial of CR as usually performed in the 'real world' showed that CR had no impact on cardiac death rates or any other outcome. Only 20–50% of eligible patients attend CR programmes and attendance at CR has not improved in the last 20 years despite major attempts to increase participation in CR. Alternative methods for provision of CR have been sought. These include home-based CR, case management approaches, and nurse coordinated prevention programmes. Telephone based programmes, such as The COACH Program, have been introduced to coach patients and improve behavioural and biomedical risk factors. These have been shown to improve risk factors better than usual patient care and to reduce recurrences of cardiac events after discharge from hospital due to MI. Expansion of novel approaches such as The COACH Program may help to counteract the non-attendance at CR.